2012
DOI: 10.1002/dta.1354
|View full text |Cite
|
Sign up to set email alerts
|

A review of analytical strategies for the detection of ‘endogenous’ steroid abuse in food production

Abstract: Detection of the abuse of synthetic steroids in food production is nowadays relatively straightforward using modern techniques such as gas or liquid chromatography coupled to mass spectrometry (GC-MS/MS or LC-MS/MS, respectively). However, proving the abuse of 'endogenous' (or naturally occurring) steroids is more difficult. Despite these difficulties, significant progress in this area has recently been made and a number of methods are now available.The aim of the current review was to systematically review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…The anabolic steroid Boldenone is used to enhance the growth of food-producing animals. Boldenone functions by stimulating receptor molecules in muscle cells resulting in the activation of specific genes, leading to protein production [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anabolic steroid Boldenone is used to enhance the growth of food-producing animals. Boldenone functions by stimulating receptor molecules in muscle cells resulting in the activation of specific genes, leading to protein production [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anabolic steroid has dual effects on humans (directly and indirectly); directly as intramuscular injection to build muscles and indirectly as through consuming meat of animals that were treated with Equigan (Scarth et al, 2012). The present results revealed that intramuscular injection of the anabolic steroid Equigan to male rats evoked a significant elevation in the food intake, fluid intake and relative body weight rate and a significant depletion in the relative testes weight in Equigan group as compared to control group while the relative weights of epididymis, seminal vesicles and prostates did not reveal any changes between the different groups under study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of anabolic pharmacologic agents as growth promoters in the farming industry may lead to residues in meat products that can cause an athlete to fail a drug test in the same way as can happen with contaminated supplements (43,44). The recent (2013) revelations that substantial numbers of beef products (burgers, ready meals, etc.)…”
Section: Supplements or Food?mentioning
confidence: 94%